Baseline Nutrition Knowledge among PKK Cadre Mothers through the SEPIRING SEHATI Program in Suci Village - Muh. Arfah; A. Titik Suhartini; Bima Ardiyanto Wibowo; Setiya Purbasari; Yunita Dyah Fitriani; Yuyun Farihatin; Aulia Rizqi Ramadhani; Nursuciyani Jamal (PROMOTOR, 2026)
Background: Balanced nutrition is a fundamental determinant of family health and has direct implications for child growth and stunting prevention. The SEPIRING SEHATI education program was designed as a community-based initiative to strengthen nutrition literacy among PKK cadre mothers in Suci Village by introducing the My Plate (Isi Piringku) concept, the use of local foods, and healthy living practices. Objective: This study aimed to describe the baseline knowledge of PKK cadre mothers in Suci Village regarding balanced nutrition before their participation in the SEPIRING SEHATI education program. Methods: This study used a descriptive analytic design with a cross-sectional survey approach. A total of 47 PKK cadre mothers who attended the SEPIRING SEHATI program on May 10, 2026, were recruited using total sampling. Data were collected using a structured 10-item Google Form questionnaire assessing knowledge of balanced nutrition principles, the My Plate concept, the role of local foods, and stunting prevention. Scores were categorized as low (0-5), moderate (6-7), or high (8-10). Results: The mean pre-test score was 9.17 (SD = 0.89), equivalent to 91.70 on a 100-point scale. Most respondents (95.7%) were classified as having high knowledge. Three indicators were answered correctly by all respondents: the understanding that balanced nutrition does not require expensive foods, the importance of handwashing as part of a healthy lifestyle, and the role of My Plate in preventing stunting. The lowest correct responses were observed for the nutritional equivalence of local foods (78.7%) and the recommended vegetable-fruit proportion in one serving plate (80.9%). Conclusion: PKK cadre mothers in Suci Village demonstrated strong baseline knowledge of balanced nutrition. However, future education should emphasize the practical application of My Plate proportions and the nutritional value of locally available foods to strengthen community-based nutrition education.